2009
DOI: 10.1108/17538290911005162
|View full text |Cite
|
Sign up to set email alerts
|

Managing change in IT outsourcing arrangements

Abstract: PurposeClients and IT outsourcing service providers are regularly confronted with changes in their business and IT environment. This paper aims at understanding the need for adaptability and the capabilities of service providers in outsourcing arrangements.Design/methodology/approachThe paper uses a combination of literature research and case study research. A retrospective view on the case study was investigated using interviews, and analyses of reports and observations.FindingsClients are dependent on their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(1 citation statement)
references
References 129 publications
(261 reference statements)
0
1
0
Order By: Relevance
“…Literature reveals that the transition phase is considered as risky and needs to be managed carefully [2] as it may influence the relationship between a client and provider significantly. Previous research [3], [4] identified that service providers generally struggle with the transition phase, often resulting in a fragile start of a service delivery that initially looked promising. These findings are consistent with market research [5] and previous studies that suggest that over two-thirds of the problems in unsuccessful engagements arise due to failed or poor transitions [6].…”
Section: Introductionmentioning
confidence: 99%
“…Literature reveals that the transition phase is considered as risky and needs to be managed carefully [2] as it may influence the relationship between a client and provider significantly. Previous research [3], [4] identified that service providers generally struggle with the transition phase, often resulting in a fragile start of a service delivery that initially looked promising. These findings are consistent with market research [5] and previous studies that suggest that over two-thirds of the problems in unsuccessful engagements arise due to failed or poor transitions [6].…”
Section: Introductionmentioning
confidence: 99%